Popularity of the Different Types of Bread in Mangalore City (International Journal of Innovative Research in Engineering & Management, 2023)
The research delves into the intriguing  realm of consumer preferences surrounding different  types of bread within the urban landscape of Mangalore  city. With a primary objective of deciphering the factors  that contribute to the varying levels of popularity among  these bread varieties, the study adopts a multidimensional  approach. By conducting comprehensive surveys and  employing rigorous data analysis techniques, the research  sheds light on the intricate interplay between cultural  influences, socioeconomic dynamics, and individual  tastes that shape the bread consumption patterns in  Mangalore. This investigation not only provides valuable  insights into the city’s gastronomic landscape but also  unravels the broader sociocultural tapestry that underlies  these culinary choices. Through a meticulous exploration  of the popularity of diverse bread types, this research  contributes to a nuanced understanding of the ever evolving dietary preferences and their implications in a  dynamic urban setting like Mangalore.Bread a food  which is full of flavors and nutrients. It is used as a basis  of our daily diet. Breads can be made in different variants  using different types of flour and other ingredients. The  tastes of all breads will differ based on the different  ingredients used in making them.
Keywords: Popularity; Bread Types; Mangalore City; Consumer Preference; Cultural Influence; Socioeconomic Factors; Consumption Patterns; Gastronomic Landscape; Sociocultural ImplicationS; Dietary Preferences; Urban Setting